Steel magnolias (2012) [videorecording (DVD)] - Harling, Robert; Robinson, Sally Beth; Queen Latifah, 1970-; Rashad, Phylicia, 1948-; Oduye, Adepero; Rashad, Condola, 1986-; Scott, Jill, 1972-; Kittles, Tory; Omilami, Afemo, 1950-; Woodard, Alfre, 1953- (Sony Pictures Home Entertainment, 2013)
Steel Magnolias is an American comedy-drama television film directed by Kenny Leon that premiered at Lifetime Network on October 7, 2012. It is the remake of 1989 film of the same name. The new film stars an all-African American cast.